Feasibility Analysis on Tempe Industrial Home (Case in Tempe Yayan Industrial Home, Lebaksiuh Village, Ciawi District, Kuningan Regency) - Yono Suryana; Aldy Prasetya; Tri Sutrisno; Achmad Faqih (Pusat Publikasi Nusantara, 2024)
This study aims to evaluate the financial viability of tempeh home industry businesses by analyzing how production costs affect profitability. The design used in this study is a quantitative descriptive method with a technical survey approach. The data collection techniques include observation, interviews, and questionnaires (questionnaires). The results of this study are as follows: (1) Total production BEP and BEP business price of Tempe Yayan's home industry business in Lebaksiuh Village, Ciawi District, Kuningan Regency, were analyzed. (2) The R/C ratio analysis was used to analyze the profit and loss of the home industry. (3) The total profit of this home industry was calculated as a function of production costs, BEP price, and total profit. (4) Based on the results of the research and discussion conducted regarding the Profit and Loss Analysis of the Tempe YaYan Home Industry Business, future research could focus on a comparative analysis of financial performance and profitability across different tempay home industry ventures in various regions. The research would provide a broader understanding of best practices and challenges faced by similar businesses, offering valuable insights for both entrepreneurs and policymakers. (5) The research could explore the impact of government support and interventions on the growth and success of home industry enterprises, particularly in terms of capital access, production efficiency, and marketing effectiveness.